GAMBARAN KESESUAIAN PERESEPAN TERHADAP KETERSEDIAAN OBAT PUSKESMAS X DI BANJARMASIN SELATAN PERIODE DESEMBER 2021 - Retna Eka Dewi (Journal of Innovation Research and Knowledge, 2023)
Appropriateness of prescribing with the availability of medicine is a cycle that influences each other with the rational use of drugs. Rational prescribing is if the patient receives treatment appropriately in doses, in periods, and at affordable cost according to his clinical needs. This study aims to describe the appropriateness of prescriptions for medicine availability at the Public Health Center X in South Banjarmasin for the period of December 2021. This type of research uses a retrospective descriptive method with samples was take by random sampling. The results showed that of the 328 prescriptions, there was an inappropriate with the type of drug found as much as 29.57%, with the drug strength found as much as 12.50%, with the dosage form found as much as 1.52%, with the duration of administration was found to be 1.22%, for the route of drug administration it had 100% appropriate. The results of this study indicate that the incompatibility of the type of drug has the highest percentage, namely 29.57%.